John H. Wigmore (1863-1943): A Mosaic that Illustrates the Development of Comparative Legal History - Parise, Agustín (2019)
This paper approaches comparative legal history in light of the life and work of John H. Wigmore. This paper first presents a definition of comparative legal history. Secondly, this paper addresses a mosaic of interests that Wigmore lived and experienced. It therefore presents a main dialogue of this jurist with the law of evidence, another dialogue with auxiliary disciplines, and a common thread that is represented by his interest in legal history and comparative law. This paper therefore points to the role that different actors may have in the development of an autonomous discipline, while they interact with other actors in other jurisdictions.